2011
DOI: 10.1007/s00011-011-0359-9
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin protects against lipopolysaccharide-induced acute lung injury in mice by alleviating inflammatory cell infiltration and microvascular permeability

Abstract: The findings suggest that PF is able to alleviate ALI, and the underlying mechanisms are probably attributed to decreasing the production of proinflammatory cytokines through down-regulation of the activation of p38, JNK and NF-κB pathways in lung tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…For example, paeoniflorin suppresses the inflammatory mediators IL-1, TNF-␣, and PGE2 in type II collagen induced arthritic rats (40). Zhou et al (43) have showed that paeoniflorin protects against LPS-induced acute lung injury through downregulation of the activation of p38, JNK, and NF-B pathways. Chen et al (2) showed that paeoniflorin suppresses TNF-␣ induced chemokine production in human dermal microvascular endothelial cells, which is relevant to NF-B and ERK pathways suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, paeoniflorin suppresses the inflammatory mediators IL-1, TNF-␣, and PGE2 in type II collagen induced arthritic rats (40). Zhou et al (43) have showed that paeoniflorin protects against LPS-induced acute lung injury through downregulation of the activation of p38, JNK, and NF-B pathways. Chen et al (2) showed that paeoniflorin suppresses TNF-␣ induced chemokine production in human dermal microvascular endothelial cells, which is relevant to NF-B and ERK pathways suppression.…”
Section: Discussionmentioning
confidence: 99%
“…no. 12-1001, HPLC Ն 98%) was obtained from Shanghai R&D Center for Standardization of Traditional Chinese Medicine, Shanghai, China, and the dosage selection (50 mg/kg) was based on previous in vivo studies and was confirmed to result in effective alleviation of acute lung injury and arthritis in mouse disease models (40,43).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, in a bleomycin-induced lung fibrosis mouse model, approximately one-third of the fibroblasts in lung tissues were derived from type II lung epithelial cells that underwent EMT [9] . Paeoniflorin ( Figure 1), a pinane monoterpene glucoside found in the root of Paeonia lactiflora Pall, has been reported to have anti-inflammatory and immunomodulatory properties [10][11][12] . Recently, we demonstrated that paeoniflorin substantially prevented pulmonary fibrosis (PF) in bleomycin-treated mice by suppressing the synthesis of type I collagen in lung tissues [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Similar effects of paeoniflorin on the severity of hind paw swelling and the scores of polyarthritis were also confirmed in the rats with experimental arthritis [19][20][21]. In addition, intraperitoneal injection of paeoniflorin inhibited the severity of intratracheal instillation of lipopolysaccharide (LPS)-induced acute lung injury in mice by suppressing inflammatory cell infiltration and lowing microvascular permeability [22]. Subcutaneous injection of TGP also inhibited capillary permeability associated with inflammation induced by intraperitoneal injection of acetic acid in mice [23].…”
Section: Anti-inflammatory Effectsmentioning
confidence: 61%